Morphological transformation in a freshwater Cyanobium sp. induced by grazers - Jezberová, Jitka; Komárková, Jaroslava (Environmental microbiology, 2007)
We document a remarkable morphological transformation, attributable to grazing by nanoflagellate Ochromonas sp. DS, of a phycocyanin-rich freshwater Cyanobium sp. (10-NR 98.2% similar 16S rRNA gene sequence to the type species Cyanobium gracile). The single cells aggregated into microcolonies (average size 40 microm) in the presence of the protist. Colonies were characterized by hundreds of tubes (spinae), 100 nm to 1 microm long and 63 +/- 6 nm wide, on the surfaces of the Cyanobium cells co-cultured with Ochromonas. Spinae production, previously unknown for the freshwater Cyanobium species, suggests that picocyanobacterial life strategies are more flexible than previously thought.
Keywords: transmisní elektronová mikroskopie; Cyanobacteria; sinice; Phenotype; buněčné výběžky; Ochromonas; fenotyp; Cell Surface Extensions; stravovací zvyklosti; Feeding Behavior; Microscopy, Electron, Transmission